Flexible Intramedullary Nails for Femur Fractures in Pediatric Patients Heavier Than 100 Pounds. Issue 2 (February 2018) - Shaha, James; Cage, Jason M.; Black, Sheena; Wimberly, Robert L.; Shaha, Steven H.; Riccio, Anthony I.
Abstract : Background: Flexible intramedullary nailing (FIMN) of femoral shaft fractures in children >100 pounds remains controversial. The purpose of this study is to assess the relationship between patient weight and alignment at radiographic union following Ender's FIMN of pediatric femoral shaft fractures. Methods: An IRB approved, retrospective review of all patients who sustained a femoral shaft fracture treated by retrograde, stainless-steel Ender's FIMN was performed at a level 1 pediatric trauma center from 2005 to 2012. Preoperative radiographs were analyzed to determine fracture pattern, location, and isthmic canal diameter. Patient weight was measured on presentation to the emergency room. Radiographs at bony union were reviewed to measure shortening, coronal angulation, and sagittal angulation. Results: A total of 261 children underwent Ender's FIMN for femoral shaft fractures during the study period. There were 24 patients who weighed ≥100 lbs and 237 patients who weighed <100 lbs. There were no significant differences in sex (75% vs. 73% male), fracture stability (42.6% vs. 41.7% length unstable), or fracture patterns between the 2 groups. The ≥100 lbs group was significantly older (10.6 vs. 8.0 y, P <0.001). There were no significant differences in final coronal angulation (1.5 vs. 3.0 degrees), sagittal angulation (2.8 vs. 3.1 degrees), or shortening (3.4 vs. 3.5 mm) between the 2 groups. There were significantly more nail removals in the <100 lbs group (81.4% vs. 66.7%, P <0.01). Four percent of the population (10 patients) weighed ≥120 lbs and aside from age (11.4 vs. 8.1 y, P <0.01), there were no significant demographic or fracture pattern differences between this group and the remaining population. This heaviest group demonstrated no significant difference in shortening (3.3 vs. 3.5 mm), coronal angulation (0.8 vs. 3.0 degrees), or sagittal angulation (0.7 vs. 3.2 degrees) at radiographic union when compared with the lighter patients. Conclusions: Stainless-steel Ender's FIMN is an effective treatment for pediatric femoral shaft fractures in patients ≥100 pounds with excellent radiographic outcomes and no increased risk for malunion. Level of Evidence: Therapeutic Level III.